The cat in the hat comes back - Dr. Seuss (London : HarperCollins Children's Books)
The Cat in the Hat returns for more out-of-control fun. It's a snowy day and Dick and Sally are stuck shoveling until the Cat in the Hat arrives to liven things up. Featuring the Cat's helpers Little Cat A, Little Cat B, and so on, and ending with a gigantic Voom
Keywords: Cat in the Hat; Fantasy; Stories in rhyme